Phenylalanine hydroxylase mRNA rescues the phenylketonuria phenotype in mice - Cacicedo, Maximiliano L.; Weinl-Tenbruck, Christine; Frank, Daniel; Limeres, Maria Jose; Wirsching, Sebastian; Hilbert, Katja; Pasha Famian, Mansure Abdollah; Horscroft, Nigel; Hennermann, Julia B.; Zepp, Fred; Chevessier-Tünnesen, Frédéric; Gehring, Stephan (Frontiers in Bioengineering and Biotechnology, 2022)
Phenylketonuria (PKU) is an inborn error of metabolism caused by a deficiency in functional phenylalanine hydroxylase (PAH), resulting in accumulation of phenylalanine (Phe) in patients´ blood and organs. Affected patients encounter severe mental retardation, neurological deficits, and behavioral abnormalities when not treated. Early diagnosis and treatment are extremely important; newborn screening programs have been implemented in most countries to ensure early identification of patients with PKU. Despite available treatment options, several challenges remain: life-long adherence to a strict diet, approval of some medications for adults only, and lack of response to these therapies in a subpopulation of patients. Therefore, there is an urgent need for treatment alternatives. An mRNA-based approach tested in PKU mice showed a fast reduction in the accumulation of Phe in serum, liver and brain, the most significant organ affected. Repeated injections of LNP-formulated mouse PAH mRNA rescued PKU mice from the disease phenotype for a prolonged period of time. An mRNA-based approach could improve the quality of life tremendously in PKU patients of all ages by replacing standard-of-care treatments.